KRISIS KEPERCAYAAN AMERIKA SERIKAT TERHADAP RUSIA DALAM PROSES MENUJU IMPLEMENTASI JOINT IMPLEMENTATION CENTER (JIC) UNTUK MENGHADAPI TERORIS DI SURIAH PADA MASA KEPEMIMPINAN BARACK OBAMA - Muthiara Yose Safitri (2020)
The impact of the Arab Spring on Syria has again confronted the United States and Russia to be directly involved as rivals in the war. However, the spread of the threat of terrorism from Iraq to Syria has prompted the two countries that take up this contradictory role to agree in making terrorists become a priority to be faced together. This paper uses qualitative research methods with primary and secondary data collection techniques through literature studies to analyze how the US crisis of trust in Russia is driving the failure of cooperation in the process of reaching JIC to combat terrorist groups in Syria. The author uses the Approach of Level of Analysis at the decision making level to explain how individual decision makers in a country can influence the resulting foreign policy. The author also uses the Theory of Trust - which plays a role in a cooperative relationship, which is associated with the concept of a security dilemma. Then, analyzing the failures that occurred starting from the policies produced by the US to cooperate with Russia, to the emergence of security dilemma that was felt by the US due to the crisis of trust in Russia when it was in a phase of a ceasefire that caused the JIC failed to form. In this case, the ceasefire seemed to be a 'temptation' for the two countries to show whether their rivalry status would not affect their 'commitment' in carrying out agreed upon matters. This paper aims to illustrate how the crisis of trust affected the cooperation between the United States and Russia which made the ceasefire agreement both difficult to survive, thus hampering the achievement of JIC. The results of this study indicates that the existence of a crisis of trust has given birth to security dilemma, thus preventing the achievement of JIC.